Crafting Briquettes for Learning: The Role of Project-Based Learning in Enhancing High School Students’ Scientific Reasoning Skills in Physics Education - Supeno, Supeno; Handayani, Rif'ati Dina; Sari, Dwi Resta Maulita (Universitas Negeri Semarang, 2025)
Physics learning in senior high school faces challenges in developing students' scientific reasoning ability. This study aims to examine students' scientific reasoning ability through project-based learning of briquette making and its effect on improving students' critical thinking ability, especially in SMA Negeri 1 Jatiroto, to improve a more effective understanding of physics. The research was conducted at SMA Negeri 1 Jatiroto, Lumajang Regency, in semester one of the 2024/2025 scholastic year. The population of the research sample was class X students, which was determined using homogeneity test and random sampling technique or purposive sampling. The research design used Quasi Experimental with pre-test and post-test. Data collection was done through tests, observations, interviews, and documentation. The pre-test and post-test results showed a significant increase in the experimental class, with a higher mean post-test result (84) than the control class (50). Data analysis displayed a significant difference between the two groups, indicating that the project-based learning model had a beneficial effect on enhancing performance students' scientific reasoning skills. Thus, project-based learning in briquette making is proven to be able to encourage increased understanding of physics concepts while developing students' critical thinking skills more effectively.